R&D Subsidies and Firms' Cost of Debt - Hanna Hottenrott; Sarah Demeulemeester (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Information asymmetry and outcome uncertainty increase the cost of debt for R&D. This study shows that recipients of public R&D grants face lower costs of debt. Immediate effects suggest that quality certification explains this observation. For younger ventures certification is accompanied by liquidity effects. Short-term effects stem from grants for research. In addition, longer-term liquidity effects point to grants facilitating young firms' investments in R&D that advance project maturity.
Keywords: O31; O38; L26; G30; 330